A Morphological Analysis of Slang Words Used by Characters in “Ralph Breaks the Internet” Movie - Norah Bt Entus Nasrudin Tubagus; Siti Suharsih; Rahman Hakim (Universitas Dian Nuswantoro, 2021)
Abstract: The current study entitled “A Morphological Analysis of Slang Words Used by Characters In Ralph Breaks the Internet Movie” aimed to investigate the morphological processes of constructing slang words and its meaning of the found slang words used by the movie characters. This research used a descriptive qualitative method with content analysis design. The findings revealed that there are 42 slang words categorized into different morphological processes included compound (14,28%), clipping (11,90%), blending (14,28%), affixations (16,66%), reduplicative (7,14%), backformation (2,4%), abbreviation (2,4%), conversion (4,76%), alternation (14,28%), extension (4,76%) and word manufacture (7,14%). This study demonstrated the meaning changes of the slang words that have been affected through certain morphological processes by modifying their word category. Consequently, some slang terms have preserved the original meaning despite the changes in their spelling. In the meantime, certain slang words get abbreviated or shortened and retained their original meaning. Meanwhile, some slang words change their meaning by deriving their word category. Besides, there were certain slang words that change their meaning depending on word usage.Key words: morphology, Ralph Breaks the Internet, slangAbstrak. Penelitian yang berjudul “Analisis Morfologi Kata-kata Slang yang Digunakan oleh karakter dalam Film ‘Ralph Breaks the Internet’” bertujuan untuk menelaah proses morfologi dalam membangun kata-kata slang dan maknanya yang digunakan dalam film tersebut. Penelitian ini menggunakan metode kualitatif deskriptif dengan desain analisis isi. Data temuan menunjukkan 42 kata slang yang dikategorikan ke dalam proses morfologi yang berbeda, yaitu ‘compound’ (14,28%), ‘clipping’ (11,90%), ‘blending’ (14,28%). , ‘affixations’ (16,66%), ‘reduplicative’ (7,14%), ‘backformation’ (2,4%), ‘abbreviation’ (2,4%), ‘conversion’ (4,76%), ‘alternation’ (14,28%), ‘extension’ (4,76%) dan ‘word manufacture’ (7,14%). Studi ini mendemonstrasikan perubahan makna dari kata-kata slang yang telah dipengaruhi proses morfologi tertentu dengan memodifikasi kategori kata asal. Hasilnya beberapa istilah dalam kata slang tetap mempertahankan makna aslinya meskipun ejaannya berubah. Sementara itu, kata-kata slang tertentu disingkat dan tetap mempertahankan arti aslinya. Beberapa kata slang lainnya berubah makna dengan mengubah kategori katanya. Selain itu, beberapa kata-kata slang tertentu berubah maknanya tergantung dari penggunaan kata.Kata kunci: morfologi, Ralph Breaks the Internet, slang